Exercise Training Increases Interleukin-10 after an Acute Myocardial Infarction: A Randomised Clinical Trial - Ribeiro, F.; Alves, A. J.; Teixeira, M.; Miranda, F.; Azevedo, C.; Duarte, J. A.; Oliveira, J. (International Journal of Sports Medicine, 2012)
The present study assessed the effects of exercise training on biomarkers of inflammation in postinfarction patients. This single-centre prospective randomized controlled trial encompassed 42 patients after the first myocardial infarction divided into exercise-training (n=22) or usual care (n=20) groups. Complete randomization was performed by choosing one of 2 sealed envelopes. The exercise-training group participated in an 8-week programme comprising 3 aerobic exercise sessions per week. The control group received usual care. The main measures were changes in circulating levels of C-reactive protein, interleukin (IL)-6 and -10, soluble vascular cell adhesion molecule-1 (VCAM-1), soluble intercellular adhesion molecule-1 (ICAM-1), anthropometrics, dietary intake, daily physical activity, and cardiorespiratory fitness. 4 patients terminated the study prematurely, leaving 38 for the statistical analysis (exercise-training, n=20; control group, n=18). In comparison to control group, exercise-training group improved IL-10 levels [1.7(7.0) vs.  − 0.3(2.4) pg/mL, P<0.05], daily moderate-intensity physical activity (12.9±21.3 vs.  − 0.7±13.4 min, P<0.05), and cardiorespiratory fitness (3.0±3.5 vs. 0.3±4.1 ml/min/kg, P<0.05). Additionally, the change in VCAM-1 and ICAM-1 levels was significantly higher in the control group (respectively, 26.6±112.1 vs. 94.1±90.0 ng/mL and 7.3±41.0 vs. 35.0±39 ng/mL, P<0.05). In conclusion, exercise training improved the inflammatory profile in post myocardial infarction patients by enhancing the anti-inflammatory cytokine IL-10.
Keywords: rehabilitation; endothelial function; inflammation; coronary artery disease